Validation of the Delone and McLean information systems success model: a study on student information system - Çelik, Kamil; Ayaz, Ahmet; Çelik, Kamil (Springer, 2022)
This study aims to evaluate the success of the Student Information System (SIS) using the updated Information System Success Model (IS success model) proposed by Delone and McLean. Survey data were collected from 882 students using SIS at a state university in Turkey. Structural Equation Model analysis was applied through R to analyze the obtained data. According to the empirical results, system quality, information quality, and service quality had a significant effect on use. However, system quality, information quality, and service quality did not significantly affect user satisfaction. In addition, both system use, and user satisfaction have no significant impact on the success of SIS. As a result, it would be beneficial for higher education institutions to evaluate the achievements of existing SISs to increase the use of SIS and student satisfaction.
Keywords: Student Information System; Information Systems Success Model; Delone And Mclean Model